The Role and Importance of Extracurricular Activities in the Formation of Moral Education - qizi, Sattorova Dilfuza Bahadir (International Journal on Human-Computing Studies, 2023)
In this article, the role and importance of extracurricular educational activities in the formation of spiritual and moral education in the school is scientifically and theoretically analyzed.